Consumption of sweeteners by patients with type 2 diabetes mellitus: an integrative review (Research, Society and Development, 2020)
The present study aimed to analyze the impact caused by the consumption of sweeteners in individuals with type 2 Diabetes Mellitus. This is an integrative review carried out using the descriptors diabetes mellitus type 2, dietary sweeteners and nutrition in the databases Bireme, PubMed and Science Direct from March to April 2019 with articles published from 2009 to 2019. Ten articles of the clinical trial type performed on individuals with type 2 Diabetes Mellitus were selected, which demonstrated the effects of the consumption of dietary sweeteners and the safety in their use by these patients. The research sample used ranged from six to 494 individuals, of both sexes and aged between 18 and 75 years. The main sweeteners studied in these articles were: aspartame, acesulfame-k, isomaltulose, sucralose, D-tagatose, arginyl fructose, stevia, pinitol and allulose. Dietary sweeteners have been found to have positive effects for individuals with diabetes. Studies have shown that the analyzed sweeteners are apparently safe to use, in addition to attributing the sweet taste to the food or preparation. It is noted that the studies available on the topic addressed are still divergent and inconclusive.